Phytochemical Screening And Antioxidant Activity Test of Lupun Root (Poikilospermum suaveolens (Blume) Merr) from South of Borneo - Mardiana, Lia; Milanda, Tiana; Hadisaputri, Yuni Elsa; Chaerunisaa, Anis Yohana (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Lupun root is the local name for Poikilospermum suaveolens (Blume) Merr. in the Aranio region, South of Borneo, Indonesia. P.suaveolens is a medicinal plant traditionally used to treat various ailments and to enhance the body’s immune function. This study aimed to investigate the secondary metabolites and antioxidant capacity of the ethanol extract derived from the root of Lupun (P. suaveolens). Samples were collected from Aranio, South Borneo. Extraction was performed by maceration using 96% ethanol. The analysis included phytochemical screening and evaluation of antioxidant activity using the DPPH (2,2-diphenyl-1-picrylhydrazyl) assay measured by a UV-Vis spectrophotometer. Phytochemical screening revealed the presence of alkaloids, flavonoids, tannins, and phenolic compounds in the Lupun root extract. The antioxidant assay showed an IC50 value of 20.44 µg/mL, indicating strong antioxidant potential of the ethanol extract. These results highlight the plant’s promise as a candidate for pharmaceutical development.